Analisis Kesulitan Mahasiswa Dalam Menyelesaikan Kasus Rancangan Percobaan - Meifiani, Nely Indra; Susanto, Hari Purnomo (Pendidikan Matematika Universitas PGRI Yogyakarta, 2016)
Over the past century, there has been a dramatic increase in worldwide research.Â However, these rapid increases are also arising problems or difficulties faced by the university students. Therefore, this research was carried out to reveal the types of those difficulties faced by students of STKIP Pacitan PGRI in solving the two-factor experiment tests in the design of experiment subject and the factors which cause these difficulties.Â The researcher opted the qualitative descriptive design to the qualified research findings. Moreover, the samples, 15 students, were randomly taken from the total population or 93 students who attended the lectures. The technique of collecting the data employed both written test and interview of the researched subject. Based on the research findings, the students were difficult in determining the source of variance (SV), the degrees of freedom (df), the Expected Mean Square (EMS), the F value. Briefly speaking, the students were difficult in the process of calculating. While, the factors that caused the difficulties were in distinguishing the state of R, drawing a conclusion from all these factors, determining the number of r (replicate), determining the removed part from EMS, being careless in equalizing the line of numerator and denominator candidate, being unable to develop formulas, and careless in the calculation.Â Keywords: kesulitan, rancangan, faktorial